2020
DOI: 10.1002/asia.202001284
|View full text |Cite
|
Sign up to set email alerts
|

Pt Nanoparticles Supported on a Dynamic Boronate Ester‐Based G‐quadruplex Hydrogel as a Nanoreactor

Abstract: Herein, we have reported a dynamic boronic ester mediated guanosine (G) based G-quadruplex hydrogel as an ideal template for in situ and 'green chemical' approach for the synthesis and stabilization of Pt NPs. 11 B NMR and FT-IR spectra reveal the formation of dynamic boronate ester bonds. The TEM images of the G-quadruplex hydrogel reveal entangled three-dimensional (3D) crosslink nanofibrillar networks with average diameter of 20 nm. Similarly, AFM images of the hydrogel show dense nanofibrillar assembly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
(100 reference statements)
1
17
0
Order By: Relevance
“…Therefore, the formation of imino-boronate ester bonds was characterized by FT-IR (Figure 2a) and 11 of G from 1729 to 1684 cm −1 in the G4NP hydrogel indicates the formation of the H-bonded G-quartet structure. 52,53 Again, the intensity of the free −NH 2 stretching frequency at 3205 cm −1 decreases after the formation of the G4NP hydrogel, suggesting the formation of an imine bond between the free amine of the NP and the aldehyde group of 4-FPBA. Furthermore, we have analyzed the 1 H NMR spectroscopy of the G4NP hydrogel to confirm the formation of imine bonds due to the reaction between the NP and 4-FPBA.…”
Section: ■ Materials and Methodsmentioning
confidence: 97%
“…Therefore, the formation of imino-boronate ester bonds was characterized by FT-IR (Figure 2a) and 11 of G from 1729 to 1684 cm −1 in the G4NP hydrogel indicates the formation of the H-bonded G-quartet structure. 52,53 Again, the intensity of the free −NH 2 stretching frequency at 3205 cm −1 decreases after the formation of the G4NP hydrogel, suggesting the formation of an imine bond between the free amine of the NP and the aldehyde group of 4-FPBA. Furthermore, we have analyzed the 1 H NMR spectroscopy of the G4NP hydrogel to confirm the formation of imine bonds due to the reaction between the NP and 4-FPBA.…”
Section: ■ Materials and Methodsmentioning
confidence: 97%
“…Recent studies have shown that the mechanical stability of hydrogels could be largely affected by the presence of NPs. 59,60 To investigate whether the rheological performance of hybrid Pt@hydrogel was influenced by inclusion Pt nanoparticles, we carried out rheological studies at a given concentration of 20 mM. The oscillatory frequency sweep analysis of Pt@hydrogel (Figure 2a) reveals that the storage modulus (G') and loss modulus The formation of Pt NPs over peptide bolaamphiphile nanofiber was further confirmed by Xray photoelectron spectroscopy (XPS).…”
Section: Synthesis Of Pt@hydrogelmentioning
confidence: 96%
“…This dynamic boronate ester bond is the key component of this dynamic G-quadruplex hydrogels. 48,49 The FT-IR spectra of 2-FPBA shows a stretching frequency peak at 1355 cm -1 corresponding to the B-O-H bond. The appearance of a peak at 1108 cm -1 for all the dried hydrogels dictates the formation of B-O-C bond.…”
Section: G-quartet Formation G-quadruplex Formationmentioning
confidence: 99%